Molecular Regulation of CBF Signaling in Cold Acclimation. (July 2018) - Shi, Yiting; Ding, Yanglin; Yang, Shuhua
Abstract : Cold stress restricts plant growth, development, and distribution. Understanding how plants transduce and respond to cold signals has long been a topic of interest. Traditional genetic and molecular analyses have identified C-repeat/DREB binding factors (CBFs) as key transcription factors that function in cold acclimation. Recent studies revealed the involvement of pivotal protein kinases and transcription factors in CBF-dependent signaling, expanding our knowledge of cold signal transduction from perception to downstream gene expression events. In this review, we summarize recent advances in our understanding of the molecular regulation of these core components of the CBF cold signaling pathway. Knowledge of the mechanism underlying the ability of plants to survive freezing temperatures will facilitate the development of crop plants with increased freezing tolerance. Highlights: Plants withstand freezing stress by triggering cold acclimation processes; the CBF-dependent pathway has a central role in cold acclimation in plants. A cold acclimation mechanism is proposed by which the cold signal is transduced from the membrane to the nucleus, leading to a series of biochemical and physiological changes in the cell and the induction of cold-responsive genes. A subset of transcriptional regulators is involved in CBF-dependent and -independent pathways that regulate cold-regulated ( COR ) gene expression. Several protein kinases are important regulators of the CBF signaling pathway, including SNF1-related protein kinases (SnRK2s), receptor-like protein kinases, and mitogen-activated protein kinases (MAPKs). The interplay of cold, light, and phytohormone signaling is important for balancing freezing tolerance and plant growth.